From intensive land use to fragmented landscapes: perspectives on cumulative impacts of mining on forests in the Brazilian Amazon. - Siqueira-Gay, Juliana (2021)
Mining entails cumulative impacts on forests not only by directly clearing land for minerals facilities construction, but also by building associated infrastructure, such as transmission lines, access roads, railways, pipelines, and terminals to transport ore, as well as attracting workforce and expanding urban areas. The impacts extend far from the leases, causing landscape-wide consequences. Proposals to expand mining in the Brazilian Amazon, including initiatives of protected areas downgrading, downsizing and degazettement (PADDD), have been discussed given the importance of the potentially affected ecosystems and their relevance for biodiversity conservation. This thesis aims at investigating the cumulative impacts of mining and associated infrastructure on forests and testing the influence of protected areas on these impacts in the Brazilian Amazon. As results, it was found that these impacts were investigated by analyzing historic land use and cover changes and calibrating a cellular automata model to simulate scenarios of PADDD in regions under pressure for development. The interplay of land use and land cover changes leading to cumulative impacts varied according to the associated industry and infrastructure required for the mining operation. Not only the extent of the cumulative impacts is relevant, but further effects in the landscape, such as habitat fragmentation. The affected forests protect unique ecosystems and provide benefits for communities at the local, regional, and global scale, evidencing the need to comprehensively assessing the long-lasting and difficult to mitigate impacts in mineral-rich areas. This research unfolded five main recommendations for addressing cumulative impacts on forests in mining regions: (i) spatial boundaries determination should tackle the dynamic of land use and land cover change across the landscape; (ii) temporal boundaries should undertake rates of changes influencing interaction and accumulation of impacts; (iii) causal relation of impacts should take into account the importance of roads as source for impacts and further effects of forest loss on biodiversity and ecosystem services; (iv) the impact evaluation should properly consider the relevance of direct and indirect impacts; (v) protecting the landscape and optimizing roads design are opportunities for impacts mitigation. Neglecting the cumulative impacts on forests in mining regions would perversely affect ecosystems and the services they provide.